2021
DOI: 10.3390/ijms22147581
|View full text |Cite
|
Sign up to set email alerts
|

Early Functional Impairment in Experimental Glaucoma Is Accompanied by Disruption of the GABAergic System and Inceptive Neuroinflammation

Abstract: Glaucoma is a leading cause of irreversible blindness worldwide, and increased intraocular pressure (IOP) is a major risk factor. We aimed to determine if early functional and molecular differences in the glaucomatous retina manifest before significant retinal ganglion cell (RGC) loss is apparent. Adenoviral vectors expressing a pathogenic form of myocilin (Ad5.MYOC) were used to induce IOP elevation in C57BL/6 mice. IOP and pattern electroretinograms (pERG) were recorded, and retinas were prepared for RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
(90 reference statements)
2
9
0
Order By: Relevance
“…Finally, the determination of IOP is difficult in this strain, possibly due to the development of corneal calcification with age, which affects the accuracy of rebound tonometry. In order to confirm the protective effect and functionally evaluate this finding, we employed a distinct mouse model of glaucoma that is reliant upon adenoviral-mediated expression of a pathogenic variant of human myocilin in the trabecular meshwork of mice [ 29 , 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the determination of IOP is difficult in this strain, possibly due to the development of corneal calcification with age, which affects the accuracy of rebound tonometry. In order to confirm the protective effect and functionally evaluate this finding, we employed a distinct mouse model of glaucoma that is reliant upon adenoviral-mediated expression of a pathogenic variant of human myocilin in the trabecular meshwork of mice [ 29 , 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated IOP causes a number of morphologic and molecular adaptations to RGCs that may aid their survival, but reduce their functional state. One example is the disruption of GABAergic signaling that occurs rapidly after IOP elevation and causes a decrease in the pERG signal [ 30 , 57 ]. It is conceivable that resolution of either metabolic or neuroinflammatory stress through PPARγ activity reverses the dysregulation and leads to the observed increase in retinal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not autoantibodies contribute to glaucomatous damage in humans remains a matter of debate, but it has also been demonstrated that POAG patients exhibit a more robust T-cell response upon stimulation with HSP 60 or HSP 27 than controls [23,172]. Thus, it is conceivable that elevated expression of HSP results in increased loading of their proteolytic fragments on major histocompatibility complex I and II, which is also expressed at elevated levels in the glaucomatous retina, that can then serve to initiate T-cell recall responses [22,173].…”
Section: Autoimmune Responsesmentioning
confidence: 99%
“…Progressive and irreversible structural changes of the optic nerve head (ONH) and the lamina cribrosa are characteristic of glaucoma [17], and it is likely that these changes increasingly compromise axonal survival in the ONH. However, there is also substantial experimental evidence demonstrating that immediate early innate immune responses, facilitated by multifactorial mechanical, hypoxic, or metabolic stresses [18][19][20][21][22], are succeeded by a sustained adaptive immune response and leucocyte translocation into glaucomatous retinas and optic nerves [23][24][25].…”
Section: Introductionmentioning
confidence: 99%